Biventricular pacing during cardiac magnetic resonance imaging. Issue 1 (12th November 2019) - Vago, Hajnalka; Czimbalmos, Csilla; Papp, Roland; Szabo, Liliana; Toth, Attila; Dohy, Zsofia; Csecs, Ibolya; Suhai, Ferenc; Kosztin, Annamaria; Molnar, Levente; Geller, Laszlo; Merkely, Bela
Abstract: Aims: We aimed to assess the effect of cardiac resynchronization on left ventricular (LV) function, volumes, geometry, and mechanics in order to demonstrate reverse remodelling using cardiac magnetic resonance (CMR) with resynchronization on. Methods and results: New York Heart Association (NYHA) Class II–III patients on optimal medical therapy with LV ejection fraction (LVEF) ≤35%, and complete LBBB with broad QRS (>150 ms) were prospectively recruited. Cardiac magnetic resonance examination was performed at baseline and at 6-month follow-up, applying both biventricular and AOO pacing. The following data were measured: conventional CMR parameters, remodelling indices, global longitudinal, circumferential, radial strain, global dyssynchrony [mechanical dispersion (MD) defined as the standard deviation of time to peak longitudinal/circumferential strain in 16 LV segments], and regional dyssynchrony (maximum differences in time between peak septal and lateral transversal displacement). Thirteen patients (64 ± 7 years, 38% male) were enrolled. Comparing the baseline and follow-up CMR parameters measured during biventricular pacing, significant increase in LVEF, and decrease in LV end-diastolic volume index (LVEDVi) and LV end-systolic volume index (LVESVi) were found. Left ventricular remodelling indices, global longitudinal, circumferential, and radial strain values showed significant improvement. Circumferential MD decreased (20.5 ± 5.5 vs. 13.4 ± 3.4, P < 0.001), while longitudinal MD did not change. Regional dyssynchrony drastically improved (362 ± 96 vs. 104 ± 66 ms, P < 0.001). Applying AOO pacing resulted in an immediate deterioration in LVEF, LVESVi, circumferential strain, global and regional dyssynchrony. Conclusion: Cardiac magnetic resonance imaging during biventricular pacing is feasible and enables a more precise quantification of LV function, morphology, and mechanics. As a result, it may contribute to a better understanding of the effects of resynchronization therapy and might improve responder rate in the future.